Comparison of the quality of life of comorbid and non-comorbid people living with HIV/AIDS in a Nigerian secondary healthcare facility - Dalhatu Muhammad Ahmad; Haruna Rashid Muhammad; Shuaibu Aliyu; Don Eliseo Lucero-Prisno (Journal of Multimorbidity and Comorbidity)
Introduction Quality of life (QoL) is a vital healthcare indicator among people living with human immunodeficiency virus (PLWHA). Assessing the effects of comorbidities on QoL among PLWHA is of clinical and public health importance. This study compared the QoL of comorbid and non-comorbid PLWHA at St. Gerard’s Catholic Hospital (SGCH), Kaduna. Methods This was a prospective cross-sectional study of 178 conveniently selected and stratified comorbid PLWHA and 172 non-comorbid PLWHA receiving care at the facility. Data was collected using a structured, interviewer-administered instrument. The QoL scores were statistically compared using the Mann‒Whitney U test. P <0.05 was considered statistically significant for all the analyses. Results Most respondents were aged 35 – 54 years (65.2% and 66.4% for comorbid and non-comorbid patients respectively), were female (70.8% and 69.2% for comorbid and non-comorbid patients respectively) and married (67.4% and 59.3% for comorbid and non-comorbid patients respectively). For all QoL domains (perception of QoL and general health, physical health, psychological health, level of independence, social relationship, environment, and spirituality/religion/personal beliefs), there was evidence the distribution of values was significantly lower in the comorbid PLWHA compared to the non-comorbid PLWHA (p<0.001), with the largest difference seen for physical health. The mean physical health (interquartile range) was 9 (7-10) and 17 (15-19) for comorbid and non-comorbid PLWHA respectively. The most prevalent comorbidities among the PLWHA were hypertension 97 (54.49%) and diabetes 36 (20.22%). Conclusion Non-comorbid PLWHA had better QoL than comorbid PLWHA in all the QoL domains and the greatest difference was observed in physical health. Special efforts should be made to improve the QoL of comorbid PLWHA.